1

´ FORMULAS
´ ´ ˜ FORMULAS BASICAS DE DERIVAC ¸ AO 1. 2. 3. 4. 5. 6. 7. 8. 9. 10. 11. 12. 13. 14. 15. 16. 17. 18. 19. 20. 21. 22. y=c y = ( u) n y = (c.un ) y =u±v y = (u.v ) ( ) y= u v y = sin u y = cos u y = tan u y = cot u y = sec u y = csc u y = arcsin u y = arccos u y = arctan u y = arccotu y = arcsecu y = arccscu y = ln u y = eu y = au y = a log u c = constante y ′ = n.un−1 .u′ y ′ = c.n.un−1 .u′ y ′ = u′ ± v ′ ′ y = u′ .v + u.v ′ ′ −u.v ′ y ′ = u .vv 2 y ′ = cos u.u′ y ′ = − sin u.u′ y ′ = sec2 u.u′ y ′ = − csc2 u.u′ u ′ ′ y = sec u. tan u.u′ ou y ′ = tan cos u .u cot u ′ ′ ′ ′ y = − csc u. cot u.u ou y = − sin u .u 1 y ′ = √ 1− .u′ u2 − 1 y ′ = √1−u2 .u′ 1 ′ y ′ = 1+ u2 .u −1 ′ y = 1+u2 .u′ 1 ′ .u′ y = u√ u 2 −1 1 y ′ = u√− .u′ u2 −1 1 ′ ′ y = u .u y ′ = eu .u′ y ′ = au . ln a.u′ 1 ′ y ′ = u·ln a .u y′ = 0

´ ´ ˜ FORMULAS BASICAS DA INTEGRAC ¸ AO 1. 3. 5. 7. 9. 11. 13. 15. 17. 19. ∫ ∫ ∫ ∫ ∫ ∫ ∫ ∫ ∫ ∫ un du = u n+1 + c (n ̸= −1) sin udu = − cos u + c sec2 udu = tan u + c sec u tan udu = sec u + c csc u cot udu = − csc u + c sec udu = ln |sec u + tan u| + c 1 sin2 udu = 1 2 u − 4 sin 2u + c −1 u √ du = sin a + c a2 −u2 1 √ du =a sec−1 u a +c u u2 −a2 u u e du = e + c
n+1

2. 4. 6. 8. 10. 12. 14. 16. 18. 20.

∫ ∫ ∫ ∫ ∫ ∫ ∫ ∫ ∫ ∫

= ln |u| + c cos udu = sin u + c csc2 udu = − cot u + c tan udu = − ln |cos u| + c cot udu = ln |sin u| + c csc udu = ln |csc u − cot u| + c 1 1 cos2 udu = 2 u+ 4 sin 2u + c 1 du −1 u = tan 2 2 a +u a ∫ a +c udv = uv − vdu + c au au du = ln a +c
du u

1

. 9. 12. .) √ t t (n = 1. 8. sec u = 1 2u cos2 u = 1+cos √2 1−cos u sin u 2 = 2 sin (u ± t) = sin u cos t ± cos u sin t u±tan t tan (u ± t) = 1tan ∓tan u tan t 2 cos 2u = 2 cos u − 1 = 1 − 2 sin2 = cos2 u − sin2 u 1−cos u sin u tan u 2 = sin u = 1+cos u 1 cos u sin t = 2 [sin (u + t) − sin (u − t)] sin u sin t = 1 2 [cos (u − t) − cos (u + t)] 1+cos u cos u 2 = 2 cos (u ± t) = cos u cos t ∓ sin u sin t sin 2u = 2 sin u cos u 2 tan u tan 2u = 1− tan2 u sin u cos t = 1 2 [sin (u + t) + sin (u − t)] 1 cos u cos t = 2 [cos (u + t) + sin (u − t)] ´ ´ FORMULAS BASICAS DA TRANSFORMADA DE LAPLACE f ( t) 1 t tn−1 (n = 1. 18. 1 s 1 s2 (n−1)! sn 1√ −3 2 2 πs 1 √ −2 F (s) = {f (t)} √ (1)(3)(5). 2.(2n−1) π 2n 1 s−a a s2 +a2 s s2 +a2 2as (s2 +a2 )2 2 s −a2 (s2 +a2 )2 (n−1)! (s−a)n (s > a) a ( s > b) (s−b)2 +a2 s−b ( s > b) (s−b)2 +a2 2as (s2 +a2 )2 s2 −a2 (s2 +a2 )2 2as2 (s2 +a2 )2 2a3 (s2 +a2 )2 πs s−n− 2 1 2 .) ebt sin at ebt cos at t sin at t cos at sin at + at cos at sin at − at cos at 1 √ t n− 1 2 1. cot u = 1 cos u. 15. 2. 6. 4. 14. 3. 7. . 2. 17. 5. . 10. 2.) eat sin at cos at t sin at t cos at tn−1 eat (n = 1. 16.´ ´ FORMULAS TRIGONOMETRICAS sin2 u + cos2 u = 1 1 + cot2 u = csc2 u u cot u = cos sin u sin u. 13. . 11. . . csc u = 1 −cos 2u sin2 u = 1√ 2 1 + tan2 u = sec2 u sin u tan u = cos u tan u. .. ..

Sign up to vote on this title
UsefulNot useful